1961
DOI: 10.1149/1.2428137
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Phase Studies in the Tantalum-Boron System between Ta and TaB

Abstract: Phase relationships in the tantalum‐boron system between Ta and normalTaB have been studied. A phase diagram of the solid portion of the system has been determined and is shown. Two three‐phase equilibria exist within the system: false(afalse)normalTa‐Ta2B‐Ta3B2 normalat 2040°±30°C , and false(bfalse)Ta2B‐Ta3B2‐normalTaB at 2180°±20°C . The chemical composition of the Ta2B phase is Ta2.4±0.2B . The composition of the Ta3B2 phase is Ta1.00±0.05B . The melting point of normalTaB lies above 2800°C. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The Cr 23 G 6 family appears much more extensive amongst the borides than the carbides, and of probably the greater general stability; but the exclusion, upon present evidence, of iron analogues (as in Fe 21 Mo 2 C 6 ) amongst the borides is notable.…”
Section: New Isomorphsmentioning
confidence: 52%
“…The Cr 23 G 6 family appears much more extensive amongst the borides than the carbides, and of probably the greater general stability; but the exclusion, upon present evidence, of iron analogues (as in Fe 21 Mo 2 C 6 ) amongst the borides is notable.…”
Section: New Isomorphsmentioning
confidence: 52%
“…As there is no relevant data on the phase of TaB in FactSage database, the Gibbs free energy change curve of TaB generated by Ta and B reaction cannot be calculated by FactSage. Therefore, CrB is used to judge the difficulty of the reaction between Ta and B, which has the same crystal structure with TaB 31–33 . Therefore, in the initial stage of high‐energy ball milling, solute tantalum tends to dissolve carbon atoms first, followed by nitrogen atoms, and then boron atoms 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CrB is used to judge the difficulty of the reaction between Ta and B, which has the same crystal structure with TaB. [31][32][33] Therefore, in the initial stage of high-energy ball milling, solute tantalum tends to dissolve carbon atoms first, followed by nitrogen atoms, and then boron atoms. 34 When the ball-milling time was less than 8 h, the diffraction peaks of mixed powders shifted to small angle gradually.…”
Section: Solid-solution Processmentioning
confidence: 99%
“…[1] and Ta~B(s) : 2.4 Ta(s) q-B(g) [2] Experimental observations showed that reaction [2] instead of reaction [1] occurred; hence the rate of loss of B(g) must be greater than 2.4 times the rate of loss of Ta(g) from Ta(s). The limiting standard free energy for reaction [2] can be computed by assuming the rate of loss of B(g) equals 2.4 times the rate of loss of Ta(g) from Ta(s). This assumption is equivalent to assuming the pressure of B(g) equals 1/9.82 times the pressure of Ta(g) over Ta(s).…”
Section: Resultsmentioning
confidence: 99%